2014
DOI: 10.1186/1471-2261-14-99
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of atorvastatin on atrial fibrillation: a meta-analysis of randomized controlled trials

Abstract: BackgroundA number of clinical and experimental studies have investigated the effect of atorvastatin on atrial fibrillation (AF), but the results are equivocal. This meta-analysis was performed to evaluate whether atorvastatin can reduce the risk of AF in different populations.MethodsWe searched PubMed, EMBASE and the Cochrane Database for all published studies that examined the effect of atorvastatin therapy on AF up to April 2014. A random effects model was used when there was substantial heterogeneity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
15
1
2
Order By: Relevance
“…38 It is known that atorvastatin is a highly effective statin medication, which is widely used in clinical treatments and is the most studied statin in relation to AF. 11 Furthermore, atorvastatin can ameliorate acute coronary syndrome by downregulating angiotensin receptors, decreasing endothelin synthesis, increasing nitric oxide bioavailability, attenuating inflammation, limiting reactive oxygen species production, and protecting against complementmediated injury. 39,40 It has been suggested that atorvastatin medications can be beneficial for protection against AF due to their anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 It is known that atorvastatin is a highly effective statin medication, which is widely used in clinical treatments and is the most studied statin in relation to AF. 11 Furthermore, atorvastatin can ameliorate acute coronary syndrome by downregulating angiotensin receptors, decreasing endothelin synthesis, increasing nitric oxide bioavailability, attenuating inflammation, limiting reactive oxygen species production, and protecting against complementmediated injury. 39,40 It has been suggested that atorvastatin medications can be beneficial for protection against AF due to their anti-inflammatory and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 It has been suggested that atorvastatin medications can be beneficial for protection against AF due to their anti-inflammatory and antioxidant properties. 11 It has been reported that atorvastatin can decrease blood lipid levels, especially cholesterol, and …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some supportive data for the use of atorvastatin in the prevention of AF post cardiac surgery, but patients need to be on it beforehand. (12) …”
Section: Primary Preventionmentioning
confidence: 99%
“…Поэтому сегодня внимание исследователей все чаще привлекают так называемые препараты upstreamтерапии, которые способны предотвращать возникновение ФП, влияя на ее субстрат. К таким препаратам относят ингибиторы АПФ, АРА-2, статины, омега-3 полиненасыщенные жирные кислоты и антагонисты МКР [17][18][19][20]. Их противоаритмическое действие обусловлено несколькими факторами: предотвращением структурного ремоделирования предсердий за счет подавления процессов фиброзирования, воспаления и оксидативного стресса, улучшением гемодинамики путем снижения артериального давления (АД) и напряжения стенок камер сердца, а также предупреждением развития или прогрессирования поражения коронарных артерий, что, как известно, является одним из важнейших факторов риска ФП [21].…”
unclassified